The Fracture Mechanical Behavior of the Interface Between Animal Fibers, Mortar, and Earth Matrices. a Theoretical and Experimental Approach - Garcia-Herrera, C; Utrera-Soto, A (Elsevier Ltd, 2023)
Theoretical-experimental research is presented to address the mechanics and failure mode of the interface between two matrices with brittle behavior, earth and mortar, and pig hair, an organic fiber that is a massive waste from the food industry worldwide. A comprehensive statistical analysis of the pull-out force is presented, accounting for the effect of fiber embedded length, diameter variability, and age of the matrices. Experimental results are contrasted with fracture-mechanics theories to describe its behavior in this matter. Results show that neither fiber length, variability of diameter, nor the age of the matrix influences the pull-out force of both matrices evaluated in this work. Our results show the brittle nature of these interfaces, which was also observed using a high-speed camera. The tensile load of the fibers was compared to the pull-out force, showing that these fibers always work within their elastic regime. This work contributes directly to the sustainable goals 9, 11, and 15 enacted by the United Nations in 2015, by contributing to the understanding of the fracture mechanics of a waste product used as reinforcement of construction matrices. © 2023 Elsevier Ltd